An empirical investigation of Borsa Istanbul single stock futures :|a TVP-VAR approach - Kalkan, Burak. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
In this thesis, the dynamic connectedness between 20 single stock futures (SSFs) of Borsa Istanbul is analyzed based on the time-varying parameter vector autoregression (TVP-VAR) methodology to evaluate the change in the degree of interconnectedness and identify which stocks are net shock transmitters or net shock receivers during turbulent times. The dynamic connectedness between spot prices, 1- month futures prices and the combination of spot and 1-month futures prices are analyzed for the period between 02.03.2016 and 07.12.2020. Results indicate that stock prices are highly interconnected during the whole period. Shock transmissions reach their highest levels during periods of increased uncertainty, currency crisis, and the outbreak of the COVID-19. Furthermore, it is found out that GARAN, AKBNK, VAKBN, ISCTR, YKBNK, and HALKB are the main net shock transmitters to the network. Also, the majority of spot prices of stocks dominate their 1-month futures prices based on the net pairwise directional connectedness. The results of this thesis can be valuable for investors, managers, and policymakers.
Keywords: Single stock futures -- Case studies.; Futures market -- Case studies.